A coordination method for concurrent design and a collaboration tool for parametric system models. (March 2018) - Knoll, Dominik; Golkar, Alessandro
This work presents a method and a tool for conducting conceptual design studies for projects such as a space exploration mission and a satellite constellation in a concurrent manner in both time and space, while taking into account the structure of the system to design and the dependencies between the system's constituting elements. Design work is parallelized to reduce the time required to converge to a solution for a preliminary design, which includes the system architecture, its detailed requirements, and its costs. The multidisciplinary team of designers works in colocation to leverage effective direct human interaction for discussing design trade-offs quickly. While this is practice in space agencies for mission feasibility studies, a common methodology was not described so far. Our work proposes a method for the coordination of discipline experts and the sequence of activities performed during conceptual design studies, which use integrated parametric system models. Our method reduces the number of design iterations by applying a design structure matrix clustering algorithm to the system model and deriving a schedule for the design session. We also describe the tool Concurrent Engineering Data Exchange Skoltech we developed for collaborative work on the parametric system models and serve as an instrument for research on complex system design methodologies. The tool features a fast synchronization mechanism for the concurrent work of multiple design experts, and it supports our coordination method for concurrent design studies. The tool was published as open-source software, so other researchers can use it and build upon it. We used our tool and applied the method to two case studies of preliminary satellite designs and tested them with groups of students of a satellite engineering class and researchers from our institute. Throughout the experiments, we recorded information about user interactions and collected user feedback for the evaluation of the coordination method and the collaboration tool. Both method and tool demonstrated their validity in our experimental setting.